Exploring the use of Assistive Digital Resources in Enhancing Learning for Students with Intellectual Disabilities in Cross River and Akwa Ibom States, Nigeria - Akin-Fakorede, Oluwaseun Omowumi; Ironbar, Virginia Emmanuel; Inaku, John Fidelis; Ekpo, Mokutima E.; Umoh, Margaret Sylvanus; Nakanda, Effiom Veronica; Agbade, Olofu Paul; Bessong, Columbus Deku; Bessong, Napoleon Osang; Ayiba, Ojong Rose; Odey, Micheal Obi; Odok, Joseph Abang; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Aim: Understanding how these digital resources are being utilized in special education contexts is essential to improving learning outcomes and bridging the digital divide for students with intellectual disabilities. The study examined the use of assistive digital resources to enhance learning for students with intellectual disabilities in Cross River and Akwa Ibom States, Nigeria. Five study objectives were stated to guide the research. Five research questions were formulated, and three hypotheses were stated. A literature review was conducted in line with the study variables. Method: This study adopted a descriptive survey research design. The area of the study is Cross River and Akwa Ibom States. The population of this study comprises all six special education and inclusive schools in Cross River and Akwa Ibom States—709 teachers, school heads, and education officers were directly involved in teaching or supporting students with intellectual disabilities—3,020 Students with intellectual disabilities (where possible, for observational data). A multi-stage sampling technique was used. A purposive sampling was used to select 4 LGAs, stratified sampling was used, and a simple random sampling technique was used. The instrument for data collection is a questionnaire, which was validated by experts in Measurement and Evaluation at the University of Uyo. The instrument was subjected to test reliability using the Cronbach Alpha reliability method. The test result revealed a reliability index of 0.81. Data from the questionnaire was analyzed using descriptive statistics (mean, frequency, percentage) and inferential statistics (Pearson correlation, independent t-test) to test the hypotheses. Results: The results revealed a significant relationship between the availability of assistive digital resources and their utilization level in teaching students with intellectual disabilities. There is also a significant relationship between the use of assistive digital resources and the learning outcomes of students with intellectual disabilities. There is a significant difference between urban and rural schools in the availability of assistive digital learning tools for students with intellectual disabilities. Conclusion: Based on the study's results, it was concluded that there is a significant relationship between the availability of assistive digital resources and their level of utilization in teaching students with intellectual disabilities. There is also a significant relationship between the use of assistive digital resources and the learning outcomes of students with intellectual disabilities. There is a significant difference between urban and rural schools in the availability of assistive digital learning tools for students with intellectual disabilities. Recommendation: Schools and disability support centers should implement peer-mentoring programs and anti-drug clubs that empower students to resist negative peer pressure.